Biological and cultural influences on disease - Mulligan, Connie (Henry Stewart Talks, 2015)
Biological and cultural influences on disease, Complex diseases: multiple genetic and environmental, Genetic factors: candidate genes and genetic ancestry, Environmental factors: toxins, and less studied factors such as race, Case study: association of candidate genes, genetic ancestry, race and socioeconomic status with blood pressure in Puerto Rico, Case study: association of candidate genes, genetic ancestry, novel measures of discrimination with blood pressure in African Americans
Reviewed at 2024/09/18